The Use of Assistive Technology to Promote Care of the Self and Social Inclusion in Patients with Sequels of Leprosy. - Fátima Beatriz Maia; Enéas Rangel Teixeira; Gislaine Valeria Silva; Maria Katia Gomes (Public Library of Science (PLoS), 2016)
This study is about the contribution of occupational therapy inside a rehabilitation group, and we focus on the autonomy of patients with disabilities due to leprosy. There are few studies on the use of assistive technology by leprosy patients; to our knowledge, none of them aim to have a subjective approach of care. Our purpose was to analyze the repercussions of assistive technology on autonomy of care of the self in patients with sequels of leprosy.A qualitative, descriptive exploratory study with a semi-structured interview and a field observation as a research method was conducted between November 2014 and February 2015 at a University Hospital in Rio de Janeiro.Eight patients from the service of Occupational Therapy were interviewed, and 44 hours of observation were performed. Interviews followed a semi-structured script and a field journal was used to take notes. Analysis was conducted by the hermeneutic approach. Costs were obtained after a global cost analysis of the fixed and variable expenses and direct and indirect costs to the manufactured products with an amount of 100 dollars. Results were grouped according to the following categories: contribution of the adapted devices for the care of the self and feelings and sensations provoked by the use of self-help devices. The reports revealed feelings, perceptions and meaningful contents about the social, familiar and individual dimensions, also the stigma coupled with leprosy. However, forms of re-signification were elaborated.Assistive technology empowers the subject to perform care of the self and promotes social inclusion.